Isolation and Characterization of Microsatellite Markers in the Domestic Ferret (Mustela putorius furo) - Ernest, Holly B. (Molecular Diversity Preservation International (MDPI), 2012)
The domestic ferret (Mustela putorius furo) is an important model organism for the study of avian influenza and other diseases of humans and animals, as well as a popular pet animal. In order to evaluate genetic diversity and study disease relationships in ferrets, 22 nuclear microsatellite loci (17 dinucleotide and 5 tetranucleotide) were developed from ferret genomic libraries and organized into seven multiplex sets. Polymorphism was preliminarily assessed in one population in Australia and one in the USA, sampled with 25 individuals each. The loci displayed allelic diversity ranging from 1 to 5 alleles, and expected and observed heterozygosities ranging from 0.04 to 0.65 and 0.04 to 0.76, respectively. Additionally, the loci amplified products in 15 samples from the wild ancestor, European polecat (Mustela putorius) and domestic ferret-polecat hybrids. In polecat/hybrid samples, allelic diversity ranged from 3 to 8 alleles, and expected and observed heterozygosities ranged from 0.13 to 0.81 and 0.13 to 0.80 respectively. These markers will be useful for molecular assessments of genetic diversity and applications to evolution, ecology, and health in domestic ferrets and wild polecats.